MAKING SERVICE LEVEL MEASURING EQUIPMENT (SERVICE DETECTOR) IN BADMINTON SPORTS - Syafani, Ali; Subarkah, Ari; Marani, Ika Novitaria (UNIVERSITAS NEGERI MAKASSAR, 2021)
This study aims to determine how to manufacture a service height measuring device in badminton. The research method used in this research was the Sugiyono model of research and development (R & D) with 5 stages from the nee analysis until field test. The research subjects for the tool trial were 25 referees and 50 men's doubles players who competed using a service height measuring device in badminton. The validation test used in this study is to use the expert justification test which consists of 1 expert lecturer in badminton and 2 referees who have BA certified. After the expert validation test was carried out, then the tool was tested and distributed a questionnaire about the attractiveness and convenience of the service level measuring device at the badminton branch. The result of this research is that measuring service stroke height using ultrasonic sensors is suitable for use in badminton matches to assist service judges in making decisions whether the service stroke is a fault or not. And based on the results of field trials, shows that measuring service stroke height using ultrasonic sensors is attractive and easy to use. The suggestion for this research is to find a tool that is more sensitive to distance and human motion or by using an application.